Lesson planning for middle school physical education meeting the national standards & grade-level outcomes - Doan, Robert John; MacDonald, Lynn Couturier 1959-; Chepko, Stevie (Human Kinetics, 2017)
Lesson Planning for Middle School Physical Education provides lesson plans from experienced middle school physical educators that: will help middle school students meet SHAPE America's National Standards and Grade-Level Outcomes; provide progressive practice tasks and integrate appropriate physical education assessments to evaluate and monitor student progress; make the best use of technology in your physical education classes; include handout materials, homework tasks, lists of needed materials and equipment, questions for student understanding, and reflection questions to ask yourself; and offer guidance on best instructional practices for involving and engaging all students. Lesson Planning for Middle School Physical Education is organized into two parts. Part I addresses important factors in planning for student success, including an introductory chapter that helps you consider the issues that influence student learning and understand the instructional environment and the scope and sequence for K-12 physical education. Part II supplies lesson plans (arranged in modules of eight lessons each) that are based on the Grade-Level Outcomes, offering you a step-by-step guide for building students' skills and knowledge in these areas: Dance and rhythms, Invasion games, Net and wall games, Fielding and striking and target games, Outdoor pursuits, Individual-performance activities, Physical activity participation outside of school, Personal fitness and fitness program design.